Tristia 1 and the Incompleteness of Ovid’s Exile Poetry - Galfre, Edoardo (Classical Journal, 2021)
This paper argues that the contrast between ostensible closure and foreseeable continuation is a crucial feature of Ovid’s first exilic book. More broadly, the exiled poet’s longing for the end of his punishment is more and more challenged by the emperor’s alleged unwillingness to recall him—which forces Ovid’s Tomitan carmen to keep on going, thus making it ultimately incomplete.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Elegiac Temporality; Exile Poetry; Limit vs. Continuation; Literary Closure; Ovid